A rare case report of coexisting rheumatic heart disease and systemic lupus erythematous - Sanjay Dhungana; Abhishek Pandey; Nijita Aryal; Kshitiz Kayastha; Santosh Pandey; Mukunda Thakur (Clinical Case Reports, 2024)
Abstract This case report discusses the rare coexistence of Systemic Lupus Erythematosus (SLE) and Rheumatic Heart Disease (RHD) in a 46‐year‐old female patient, challenging the conventional understanding of their distinct presentations. The patient exhibited migratory joint pains, palpitations, and shortness of breath. Diagnostic investigations confirmed SLE based on EULAR/ACR criteria, with positive anti‐nuclear and anti‐dsDNA antibodies. Concurrently, transthoracic echocardiography revealed severe mitral stenosis and regurgitation, leading to the diagnosis of RHD. The patient underwent successful open‐heart surgery with mitral valve replacement. The discussion explores the rarity of this coexistence, emphasizing the need for cautious consideration and further research into potential immunological overlaps between SLE and RHD. The report concludes with a call for comprehensive studies to enhance our understanding of the pathophysiology connecting these two conditions.